Myotonia Congenita: Clinical Characteristic and Mutation Spectrum of CLCN1 in Chinese Patients - Hu, Chaoping; Shi, Yiyun; Zhao, Lei; Zhou, Shuizhen; Li, Xihua (Frontiers in Pediatrics, 2021)
Background CLCN1-related myotonia congenita (MC) is one of the most common form of non-dystrophic myotonia, in which muscle relaxation is delayed after voluntary or evoked contraction. However, there is limited data of clinical and molecular spectrum of MC patients in China. Patients and Methods Five patients with myotonia congenita due to mutations in CLCN1 gene were enrolled, which were identified through trio-whole exome sequencing or panel-based next generation sequencing test. The clinical presentation, laboratory data, electrophysiological tests, muscular pathology feature and genetic results were collected and reviewed. We also searched all previously reported cases of MC patients with genetic diagnose in Chinese populations, and their data was reviewed. Results The median onset age of 5 patients was 3.0 years old, ranging from 1.0 to 5.0 years old, while the median age of admit was 5.0 years old, ranging from 3.5 to 8.8 years old. Five patients complained of muscle stiffness when rising from chairs or starting to climb stairs (5/5, 100.0%), 4 patients complained of delayed relaxation of their hands after forceful grip (4/5, 80.0%), all of which improved with exercise (warm-up phenomenon) (5/5, 100%). Electromyogram was conducted in 5 patients, which all revealed myotonic change (100%). Genetic tests revealed 9 potential disease-causing variants in CLCN1 gene, including 2 novel variants: c.962T>A (p.V321E) and c.1250A>T (p.E417V). Literature review showed 43 MC Chinese patients with genetic diagnosis have been reported till now (including our 5 patients). Forty-seven variants in CLCN1 gene were found, which consisted of 33 missense variants, 6 nonsense variants, 5 frame-shift variants, and 3 splicing variants. Variants in exon 8, 15, 12 and 16 were most prevalent, while the most common variants were c.892G>A (p.A298T) (n=9), c.139C>T(p.R47W) (n=3), c.1205C>T(p.A402V)(n=3), c.1657A>T (p.I553F)(n=3), c.1679T>C (p.M560T)(n=3), c.350A>G (p.D117G)(n=2), c.762C>G(p.C254W)(n=2), c.782A>G (P.Y261C)(n=2), and c.1277C>A (p.T426N)(n=2). Conclusion Our results reported 5 CLCN1-related MC patients, which expanded the clinical and genetic spectrum of MC patients in China. Based on literature review, 43 MC Chinese patients with genetic diagnosis have been reported till now, and variants in exon 8 were most prevalent in Chinese MC patients while c.892G>A (p.A298T) was probable a founder mutation.